Pengaruh Pengetahuan Merek Hijau dan Sikap atas Merek Hijau terhadap Niat Beli Produk Hijau Brand Fashion Nike pada Masyarakat Indonesia - Ichsan Rizal; Muchsin Muthohar (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research is intended to examine the influence of green purchase intentions using a non-probability sampling method using selected respondent criteria including Indonesian people, especially those who know or have heard about Nike brand products. Researchers used 150 respondents using Google Form. The data that has been obtained then process use the PLS-SEM software tool. The variables used in this research are green brand knowledge, attitude towards green brands, and green purchase intention. Researchers found that green brand knowledge and green brand attitudes influence green purchase intentions. This research also shows that green knowledge influences a person's attitude towards green purchasing intentions. This research is also aimed at green marketing, especially the Nike Brand, in order to increase purchasing intentions for environmentally friendly products from the Nike brand.